The level of preparedness of primary school teachers, in the disadvantaged northern areas of Port Elizabeth, to manage HIV/AIDS in the classroom - Floors, Paulus (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2009.